Salvage treatment strategies for refractory sudden sensorineural hearing loss—a comprehensive review and meta-analysis with practical recommendations - Meliante, Piero Giuseppe; D’Avino, Luigi; Barba, Giuseppe; Covelli, Edoardo; Petrella, Carla; Barbato, Christian; Minni, Antonio (Frontiers in Neurology, 2025)
BackgroundSudden sensorineural hearing loss (SSNHL) affects up to 27 per 100,000 people annually, with more than half not regaining full hearing after following standard therapy. Identifying effective salvage treatments for refractory cases is critical to improve outcomes and reduce long-term auditory disability. This systematic review aims to assess the effectiveness of current salvage treatments for SSNHL unresponsive to first-line systemic corticosteroid therapy, and to develop an evidence-based treatment algorithm.MethodsA comprehensive search of PubMed, Embase, and Cochrane Library was performed for English language articles published between January 2010 and April 2025. Studies eligible for inclusion were clinical trials and large case series that evaluated salvage interventions in patients with SSNHL who were unresponsive to systemic therapy. Risk of bias was assessed using the risk of bias in non-randomized studies of interventions (ROBINS-I) tool.ResultsA total of 41 articles met the inclusion criteria. Intratympanic steroids (ITS), including methylprednisolone and dexamethasone, showed consistent effectiveness, with methylprednisolone achieving better results (p < 0.05). Hyperbaric oxygen therapy (HY) was also effective, particularly at low frequencies. Combined ITS and HY yielded the best results in word recognition and pure-tone average (PTA) improvement, although they were not always statistically better than monotherapy. Early initiation of ITS was associated with improved outcomes, and ITS proved especially effective for high-frequency SSNHL and tinnitus (p = 0.002). Non-invasive therapies, such as constraint-induced sound therapy (CIST), have been promising in improving outcomes by decreasing maladaptive cortical reorganization. Additional emerging treatments [e.g., insulin-like growth factor 1 (IGF-1), urokinase, and surgical interventions] show potential but need further validation.ConclusionITS and HY, especially when combined, are the most effective salvage therapies for refractory SSNHL. Methylprednisolone may offer better outcomes than dexamethasone, and early intervention continues to be a crucial prognostic factor. CIST showed promising potential in reducing cortical maladaptation to sound deprivation.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42025645069, Identifier, CRD42025645069.